Keberhasilan dan Kegagalan Indonesia dalam Kebijakan Kontraterorisme - Wisesa, Raka Gusfi (Jurnal Diplomasi Pertahanan, 2021)
The threat of terrorism as an international political agenda has become a specialconcern in the discussion of all global institutions in the world in the field of defenseand security. In an effort to deal with the threat of counterterrorism, Indonesia as acountry is also involved in facing the threat of terrorism. For more than 20 years,Indonesia has pursued policies to tackle counterterrorism. This article discusses andevaluates how Indonesian policies address terrorism and its implications for thedevelopment of counterterrorism in Indonesia. The author departs from theassumptions and theories of terrorism, counter terrorism, and realism in the review ofnational security. The author concludes that there needs to be an interdisciplinarystudy involving both military and non-military aspects, strategic efforts in makingcounter-terrorism policies, and the existence of resolutions that make terrorism afactor.Keywords: decolonialization, defense diplomacy, national security, counter terrorism